Analysis of multi-criteria project selection techniques - Sheiko, I. А.; Nassuf Hamidou (ХНУРЕ, 2021)
The multi-criteria problem consists of multiple criteria/objectives that need to be optimized simultaneously. A lot of economic problem should be solved by multi criteria methods. And one of such problems is investment selection
Keywords: бізнес-освіта; стратегії економічного розвитку